Individual risk propensity and risk background - Bernard, April (Central Bank of Barbados [St. Michael]BB, 2007)
Considers the role that socio-psychological and socio-cultural factors play in individual decisions to take risk. Finds that gender had a significant influence on the probability of engaging in investment and every day risk decisions, but a relatively insignificant impact on insurance decisions.